Using the Practice of Modeling to Support Preservice Teachers' Reflection on the Process of Teaching and Learning. Issue 7 (3rd October 2017) - Zangori, Laura; Friedrichsen, Patricia J.; Wulff, Eric; Womack, Andrew J.
ABSTRACT: We studied how the practices of modeling supported preservice teachers (PSTs) as a reflection tool for knowledge integration in their science methods courses. In this exploratory study, elementary ( n  = 4) and middle/secondary ( n  = 7) PSTs drew models of the process of teaching and learning, including what occurred before, during, and after teaching. Data sources included initial and final models, explanations of initial and final models, and pre- and postinterviews. We used the knowledge integration framework to explore how the PSTs' models of the process of teaching and learning changed over time and how the PSTs perceived the value of modeling the process of teaching and learning. Results indicated that developing models supported the elementary PSTs in integrating lesson planning into their conceptions of teaching, as the planning process was previously an invisible component of teaching. Among the middle/secondary PSTs, we found that modeling supported them in integrating previously disconnected ideas into purposely linked ideas about teaching and learning as well as linking their own reflections about their teaching practice to classroom-based evidence. Finally, across the elementary and middle/secondary PSTs, we found that in drawing final models and comparing them to their initial models, they were able to identify weaknesses in their initial models and saw their individual growth in teacher knowledge during the semester. Overall, the PSTs valued the modeling activity and saw their models as a reflection tool that helped them make sense of their methods coursework. Implications for teacher educators are given.